A Diagnostic Study of Entrepreneurial Education Readiness in the Humanities and Social Sciences in Palestine - Daragmeh, Abdelkarim; Halabi, Aya (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
The humanities majors are plummeting worldwide. Experts believe that the main reason for the down drop in demand in majors like History, Archaeology, tourism, social sciences, and even foreign languages can be partially attributed to the fact that the designed curriculum no longer lives up to students’ expectations or satisfies the market’s evolving needs. In Palestine, these disciplines are confronted with the crisis of low enrolment. This diagnostic study aims to assess entrepreneurial readiness in the colleges of humanities in Palestine in order to assist education leaders in making informed decisions about the struggle of low demand and high unemployment rates. To that end, the study espoused a mixed-method approach to assess the scale and the scope of introducing Entrepreneurship Education within the Colleges of Humanities in Palestine. The researchers collected study data through focus group interviews with the deans and administrators and through surveying a random sample of the humanities teachers. The results show there is a sufficient number of teachers who use efficient teaching approaches like competency-based education or problem-based learning. Nonetheless, humanities curricula does not involve students directly in the entrepreneurial process. Current practices display lack of emphasis on training 'For' building entrepreneurial competencies or 'Through' experiential, process-based approaches that link education to the outside business environment.  Incubation services and work spaces are available on campus, but they are rarely utilized by the teachers or students from the humanities disciplines. The in-class induction strategies and the assessment methods remain very orthodox. Finally, this study provides ample evidence to support deans, administrators, and faculty members who want to systematically bring entrepreneurship into their discipline, and to deepen staff expertise in entrepreneurship education. Research paper Keywords: Entrepreneurship Curriculum, Humanities, Social sciences, Higher education, Palestine Reference to this paper should be made as follows: Daragmeh, A., & Halabi, A. (2023). A Diagnostic Study of Entrepreneurial Education Readiness in the Humanities and Social Sciences in Palestine. Journal of Entrepreneurship, Business and Economics , 11 (1), 63–101.